2018
DOI: 10.1088/1361-6528/aadbf7
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of self-assembled carbon nanotubes/dye composite films for sensitive electrochemical determination of Cd(II) ions

Abstract: A new type of voltammetric sensor material has been fabricated via a facile self-assembled method. A modified glassy carbon electrode (GCE) by phenylsulfonic groups grafted multi-walled carbon nanotubes (CNT-SOH) with dye molecules via Langmuir-Blodgett (LB) assembling (CNT-SOH/dye-LB/GCE) were prepared for detecting trace levels of cadmium (Cd) ions by square wave anodic stripping voltammetry. The synergy effect between CNT-SOH and dye as well as orderly aggregates in composite LB films contributed to greatly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…The saturation magnetization of the prepared Fe 3 O 4 nanoparticles was 83.0 emu g À1 , which is more than the values reported for other pure Fe 3 O 4 nanocrystals. [56][57][58][59] In addition, the saturation magnetization value of the Fe 3 O 4 -Ag nanocomposite was 63.2 emu g À1 . These results indicate the successful preparation of the Fe 3 O 4 -Ag nanocomposite with a coating of Ag nanowires.…”
Section: Characterization Of Fe 3 O 4 -Ag Nanocompositementioning
confidence: 94%
“…The saturation magnetization of the prepared Fe 3 O 4 nanoparticles was 83.0 emu g À1 , which is more than the values reported for other pure Fe 3 O 4 nanocrystals. [56][57][58][59] In addition, the saturation magnetization value of the Fe 3 O 4 -Ag nanocomposite was 63.2 emu g À1 . These results indicate the successful preparation of the Fe 3 O 4 -Ag nanocomposite with a coating of Ag nanowires.…”
Section: Characterization Of Fe 3 O 4 -Ag Nanocompositementioning
confidence: 94%
“…The degradation kinetics were well fitted by the pseudo-first-order model shown in Figure 12d, and the theoretical De (the degradation amount at the degradation equilibrium) value was 146 mg g −1 , which was in good agreement with the experimental data. This analysis result indicated that the pseudo-first-order model could effectively describe the MB degradation process in MnO nanomixtures [45,46,47,48,49,50,51,52].…”
Section: Resultsmentioning
confidence: 96%
“…Good stability and reusability of the adsorbent are important considerations for practical production. Adsorbents with excellent reusability have been reported in previous studies [51,52,53,54,55,56,57,58]. For example, Lu et al [41] investigated the reuse efficiency of the PDA/PEI@PVA/PEI composite adsorbent on Ponceau S (PS) of up to 91% after ten times cycling, suggesting excellent stability and recycling ability.…”
Section: Resultsmentioning
confidence: 99%